Interactive map of UiTM Shah Alam / Haslina Mohamad - Mohamad, Haslina (2007)
This project was prepared according to multimedia application in developing interactive map system for UiTM Shah Alam. This project is mainly focus to create interactive system based on the design and the ability of the system to attract users. Currently, many applications were developed in attempt to create many tools that use as a user guideline in traveling. We know that map is mainly use as a tool to guide user to move anywhere and anytime. Unfortunately, this map cannot provide a good direction to user to understand their traveling in detail. Therefore interactive map was developing to enhance the application of map. Consequently, this project takes an opportunity to develop interactive map for UiTM Shah Alam in using multimedia application and at the same time able to solve traveling problem in UiTM area. This project was develop to assist people whose travel in UiTM area whether for studies, visiting, convocation and others activity. This system is useful for them to more understand about UiTM Shah Alam road and direction. This system can use where user can access through UiTM website where is operate anytime and anywhere. This system was developing using ADDIE model which consist of five phase which are analysis, design, develop, implementation and evaluate. This system is developing by using Macromedia Director, Macromedia AdodePhotoshop and Autocadd.